QUESTIONING STRATEGIES BY TEACHERS AT PRESCHOOL LEVEL AND PATTERNS OF STUDENT RESPONSES: THE CASE OF GRAPESEED ENGLISH CURRICULUM = CHIẾN LƯỢC ĐẶT CÂU HỎI CỦA GIÁO VIÊN TIẾNG ANH Ở BẬC MẦM NON VÀ ĐẶC ĐIỂM PHẢN HỒI CỦA HỌC SINH NGHIÊN CỨU VỚI CHƯƠNG TRÌNH TIẾNG ANH GRAPESEED - Nguyễn, Hải Yến (2020)
For foreign language learners, especially young learners at kindergarten level,